Penerapan Demokrasi Pancasila dalam Proses Pemilihan Pengurus Senat Mahasiswa Farmasi Universitas PGRI Adi Buana Surabaya - Sabila Nur Aisyah; Maria Wona Gati; Mariana Helenora; Kumala Irmawati; Ditta Tri Ayundinarta; Fadhila Irawati; Ahmad Fauzan Rizqullah; Aura Putri Ayunda; Siti Khotijah; Tasya Agustin; Ellya Fauzia; Rizqy Aulia Kusman; Suyono Suyono (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
The aim of this research is to determine the application of Pancasila democracy in the process of selecting administrators for the 2023 UNIPA Surabaya Pharmacy Student Association. This research uses a qualitative method with a descriptive approach and is supported by primary data. This qualitative research was located at the Faculty of Science and Health using interview techniques to obtain data. The research results show high student participation, reflecting a strong democratic spirit. However, there are challenges related to the dominance of the candidate’s popularity and the lack of deep understanding of the values of Pancasila. The role of the election committee has proven important in maintaining the integrity and transparency of the democratic process. The findings highlight the importance of political education and election outreach to increase students’ understanding of Pancasila values and responsibilities as voters. The election process is also a vehicle for character learning for students, honing leadership skills, negotiation and practicing Pancasila values in student organizations. Recommendations include stricter regulations, integration of Pancasila values in the curriculum, as well as increasing student outreach and participation as steps to strengthen democracy and Pancasila values in the campus environment. This research provides in-depth insight into how Pancasila values are applied in the democratic life of students and provides a basis for increasing awareness and respect for these values in the future.